Effect of synthetic protease inhibitors of the amidine type on cell injury by Rickettsia rickettsii. - Walker, D H (1984)
To evaluate the importance of proteolytic activity in the pathogenesis of cell injury by Rickettsia rickettsii, a series of four aromatic amidine inhibitors of trypsin-like proteases were introduced into the plaque model. The compounds were shown to be active toward plaque reduction with their order of effectiveness parallel to their antitrypsin activity. One of the compounds, bis(5-amidino-2-benzimidazolyl)-methane, at a concentration of 10(-5) M demonstrated complete inhibition of plaque formation on day 6. Bis(5-amidino-2-benzimidazolyl)methane at the same concentration reduced cell injury even when added to the system after 72 h of rickettsial infection. The reduction in morbidity in guinea pigs experimentally infected with R. rickettsii and treated with bis(5-amidino-2-benzimidazolyl)methane as compared with morbidity in infected, untreated animals, comprised delay in the onset of fever and slightly fewer febrile animals. Because bis(5-amidino-2-benzimidazolyl)methane had no effect on phospholipase A2, the enzyme activity associated with penetration-induced cell injury, it is likely that a trypsin-like protease also plays an essential role either in the physiology of R. rickettsii or as its pathogenic mechanism.